tRNA/mRNA Mimicry by tmRNA and SmpB in Trans-Translation - Daisuke Kurita; Akira Muto; Hyouta Himeno (Journal of Nucleic Acids)
Since accurate translation from mRNA to protein is critical to survival, cells have developed translational quality control systems. Bacterial ribosomes stalled on truncated mRNA are rescued by a system involving tmRNA and SmpB referred to as trans-translation. Here, we review current understanding of the mechanism of trans-translation. Based on results obtained by using directed hydroxyl radical probing, we propose a new type of molecular mimicry during trans-translation. Besides such chemical approaches, biochemical and cryo-EM studies have revealed the structural and functional aspects of multiple stages of trans-translation. These intensive works provide a basis for studying the dynamics of tmRNA/SmpB in the ribosome.